2019
DOI: 10.1002/jsfa.9612
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties to support fibre characterization in monogastric animal nutrition

Abstract: BACKGROUND The aim of the study was to rank conventionally used fibre rich feeds for their physicochemical properties and detect possible correlation between analytical fibre determinations. A total of 22 samples were analysed for proximate fibre values, soluble dietary fibre (SDF), insoluble dietary fibre (IDF), crude protein (CP) and crude ash (CA). Physicochemical properties were determined in vitro by hydration capacity (HC) [water holding capacity (WHC), water binding capacity (WBC), swelling property (Sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 36 publications
(91 reference statements)
1
30
0
2
Order By: Relevance
“…In another study with dual purpose hens, the feeding of 10% lignocellulose temporally reduced excreta DM content while excreta viscosity was not affected ( Röhe et al., 2020 ). Compared to other insoluble NSP sources, lignocellulose shows a high water holding capacity ( Slama et al., 2019 ). The higher the water holding capacity of a dietary component, the lower the free water content in the digesta ( Takahashi et al., 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…In another study with dual purpose hens, the feeding of 10% lignocellulose temporally reduced excreta DM content while excreta viscosity was not affected ( Röhe et al., 2020 ). Compared to other insoluble NSP sources, lignocellulose shows a high water holding capacity ( Slama et al., 2019 ). The higher the water holding capacity of a dietary component, the lower the free water content in the digesta ( Takahashi et al., 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alfalfa showed with a 338% SC, an almost twice as high SC ability compared to oat fibre with a SC of 175%. The correlation of methods was positive between WBC, WHC and SC for most ingredients and it makes sense to use the physical methods of investigation to rank fibre sources [5]. As our results and the literature show, it is necessary to use the physical parameters to qualify the fibre sources and to design a feed based on these values as well as to Fig.…”
Section: Physical Characteristics Of Feed Componentsmentioning
confidence: 55%
“…For further optimising fibre supply of pigs, physical parameters analysed by standardised, feasible methods could help to develop new dietary concepts. As a study [5] has already shown, there are different methods for investigating feed with regard to their physical parameters such as SC, viscosity and WBC. It is known that the processing of feed such as grinding has an effect on the measurement results in the laboratory [41,42].…”
Section: Digestibility Of a New Fibre Combination In Diets For Pregnamentioning
confidence: 99%
See 1 more Smart Citation
“…En consideración a fundamentos de digestión y metabolismo de rumiantes, obliga a emprender experiencias que aporten información para mejorar el manejo de la alimentación en bovinos (Arai, 2014). Los asesores en alimentación y criadores de ganado deben acomodar sus recomendaciones y propuestas de raciones, tomando en cuenta los fundamentos de digestión, fisiología de la nutrición, establecer una ración de acuerdo al tipo y nivel de producción de los animales (Slama, et al, 2019).…”
Section: Introductionunclassified